PENILAIAN KINERJA PELAYANAN PUBLIK BERDASARKAN KEP/25M.PAN/2/2004 PADA KANTOR PERTANAHAN KOTA SURABAYA II - Afriani, Dian (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This pupose research is to find out the service performance which is measured by using KEP/25/M.PAN/2/2004, there are 14 service elementsand the measurement in accordance with the land office of Surabaya city II and to analyze the influence of service elements to the community satisfaction. The sample was 200 respondents from public service users at the Land Office in Surabaya II and selected by accidental sampling. The primary data source in this research from questionnaire. The analytical method used is factor analysis and multiple linear regression analysis. Through the CSI calculation obtains the index value is 2.89 and the CSI value is 72.26. Based on this result it can be concluded that the quality of land office of Surabaya city II is in good category âBâ.The calculation result of customer satisfaction survey in accordance with land office of Surabaya city II obtains score 2.24 which means that the service quality is in grade âAâ status that is very good. Through factor analysis, 14 elements of the service have been grouped into 3 factors, which are schedule certainty, environmental comfort, and reasonable cost. The result of research shows that schedule certainty, environmental comfort, and reasonable cost have positive influence to the community satisfaction.Keywords:schedule certainty (KJ), environmental comfort (KL),reasonable cost (KB),community satisfaction (KM).